High-Salt Diet Induces IL-17-Dependent Gut Inflammation and Exacerbates Colitis in Mice - Aguiar, Sarah Leão Fiorini; Miranda, Mariana Camila Gonçalves; Guimarães, Mauro Andrade Freitas; Santiago, Helton Costa; Queiroz, Camila Pereira; Cunha, Pricila da Silva; Cara, Denise Carmona; Foureaux, Giselle; Ferreira, Anderson José; Cardoso, Valbert Nascimento; Barros, Patrícia Aparecida; Maioli, Tatiani Uceli; et al. (Frontiers in Immunology, 2018)
Excess intake of sodium is often associated with high risk for cardiovascular disease. More recently, some studies on the effects of high salt diets have also demonstrated that they are able to activate Th17 cells and increase severity of autoimmune diseases. The purpose of the present study was to evaluate the effects of a diet supplemented with NaCl in the colonic mucosa at steady state and during inflammation. We showed that consumption of high salt diet (HSD) by mice triggered a gut inflammatory reaction associated with IL-23 production, recruitment of neutrophils and increased frequency of the IL-17-producing type 3 innate lymphoid cells (ILC3) in the colon. Moreover, gut inflammation was not observed in IL-17-/- mice but it was present, although at lower grade, in RAG-/- mice suggesting that the inflammatory effects of high salt diet was dependent on IL-17 but only partially on Th17 cells. Expression of SGK1, a kinase involved in sodium homeostasis, increased 90 minutes after ingestion of 50% NaCl solution and decreased 3 weeks after HSD consumption. Colitis induced by oral administration of either dextran sodium sulfate (DSS) or 2,4,6-trinitrobenzenesulfonic acid (TNBS) was exacerbated by HSD consumption and this effect was associated with increased frequencies of RORt+ CD4+ T cells and neutrophils in the colon. Therefore, our results demonstrated that consumption of high-salt diet per se triggered a histologically detectable inflammation in the colon and also exacerbated chemically-induced models of colitis in mice by a mechanism dependent on IL-17 production most likely by both ILC3 and Th17 cells.